Mechanical force-induced interlayer sliding in interfacial ferroelectrics - Zhao Guan; Lu-qi Wei; Wen-cheng Fan; Yi-chen Sun; Wei Cao; Ming Tian; Neng Wan; Wen-yi Tong; Bin-bin Chen; Ping-hua Xiang; Chun-gang Duan; Ni Zhong (Nature Communications)
Abstract Moiré superlattices in two-dimensional stacks have attracted worldwide interest due to their unique electronic properties. A typical example is the moiré ferroelectricity, where adjacent moirés exhibit opposite spontaneous polarization that can be switched through interlayer sliding. However, in contrast to ideal regular ferroelectric moiré domains (equilateral triangles) built in most theoretical models, the unavoidable irregular moiré supercells (non-equilateral triangles) induced by external strain fields during the transfer process have been given less attention. Manipulation of controllable polarization evolutions is also a big challenge due to an interlinked network of polarized domains. In this study, we employ a sliding-disturb measurement to examine and modulate these irregular moirés via mechanical force. By introducing a curved substrate, the irregular moirés are fabricated, and three distinct types of moiré domains with different patterns are identified and modulated by external mechanical force disturbing. They exhibit reduced pinning forces when the shear direction is not aligned with the strain direction. The shift of the moirés is observed to be orthogonal to the shear direction. This work offers an effective pathway for the controlled switch of the polarization in interfacial ferroelectricity.